Teacher-Centered Intelligent Tutoring Systems: Design Considerations from Brazilian, Public School Teachers - Rodrigues, Luiz; Guerino, Guilherme; Challco, Geiser Chalco; Veloso, Thomaz Edson; Oliveira, Lívia; Penha, Rodolfo Sena da; Melo, Rafael Ferreira; Vieira, Thales; Marinho, Marcelo; Macario, Valmir; Bittencourt, Ig Ibert; Isotani, Seiji; et al. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na Educação, 2023)
While Intelligent Tutoring Systems (ITSs) might enhance learning with personalized instruction, the active involvement of teachers is crucial in achieving the best results. However, teachers have not been adequately involved in the design and usage of ITSs, leading to a research gap in understanding their needs and contexts as well as designing teacher-centered ITSs. To address this gap, we present a qualitative study based on semi-structured interviews with elementary school math teachers in Brazil. Our findings reveal insights connecting teachers’ current practices with their needs, providing design considerations for teacher-centered ITSs. The study emphasizes the importance of curriculum alignment, adaptive scaffolding, comprehensive assessment mechanisms, personalized instruction, and support for teaching challenges. Our findings contribute to designing and developing ITSs tailored for Brazilian public school teachers, considering limited technology access and connectivity issues.